Respons Pertumbuhan Vegetatif Tiga Varietas Kelapa Sawit di Pre Nursery Pada Beberapa Media Tanam Limbah - Muhammad Afrillah; Ferry Ezra Sitepu; Chairani Hanum (Jurnal Agroekoteknologi, 2015)
The aim of the research was to study vegetative growth response of three varieties of palm oil tree at some palm waste as planting medium in pre nursery. The research has been conducted in Kompleks Medan permai on November 2014 to February 2015. The research design used randomized block design with two factor. The first factor was composition palm waste for planting medium (top soil, top soil + fiber 1:1, top soil + empty fruit bunches1:1, top soil + solid decanter 1:1 and top soil + fiber + empty fruit bunches + solid decanter 1:1:1:1) and the second factor was palm tree varieties (Yangambi, Simalungun, and Avros). Result from the research determined that treatment of planting medium significant effect to shoot length and stem diamer (12 and 14 week after showing), shoot wet weight and root dry weight. Yangambi, Simalungun and Avros not responding for planting medium composition. The best planting medium combination from this study were : top soil : fiber : empty fruit bunches : solid decanter (1:1:1:1).Keywords: Varieties, Planting media, palm oil